2021
DOI: 10.3390/e23020171
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning for Bit-Flipping Decoding of Polar Codes

Abstract: A traditional successive cancellation (SC) decoding algorithm produces error propagation in the decoding process. In order to improve the SC decoding performance, it is important to solve the error propagation. In this paper, we propose a new algorithm combining reinforcement learning and SC flip (SCF) decoding of polar codes, which is called a Q-learning-assisted SCF (QLSCF) decoding algorithm. The proposed QLSCF decoding algorithm uses reinforcement learning technology to select candidate bits for the SC fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Doan et al [383], [384] Neural DSCF with trainable bit-flipping metric. Wang et al [385] Q-learning-assisted SCF decoding algorithm. Doan et al [386] RL-based bit-flipping strategy for fast SC decoding.…”
Section: Dl-aided Scf Decodingmentioning
confidence: 99%
See 1 more Smart Citation
“…Doan et al [383], [384] Neural DSCF with trainable bit-flipping metric. Wang et al [385] Q-learning-assisted SCF decoding algorithm. Doan et al [386] RL-based bit-flipping strategy for fast SC decoding.…”
Section: Dl-aided Scf Decodingmentioning
confidence: 99%
“…In [383], [384], the authors proposed neural DSCF decoding where they properly approximated and introduced trainable parameters to the BF metric and optimized its parameter by RMSProp, a variant of the SGD optimization technique. In [385], the authors proposed a Q-learning-assisted SCF decoding algorithm that selects the candidate flipping bits through the learned Q-table instead of metric sorting. It was demonstrated that the proposed decoding algorithm is particularly effective in reducing the decoding delay caused by sorting during the decoding process without sacrificing performance.…”
Section: Dl-aided Sclf Decodingmentioning
confidence: 99%